Formation and occurrence of transformation products of metformin in wastewater and surface water - Tisler, Selina; Zwiener, Christian (The Science of the total environment, 2018)
The aim of this work was to investigate the occurrence and fate of the antidiabetic metformin (MF) and its transformation products (TPs) in wastewater and surface water samples. New TPs of MF were approached by electrochemical degradation with a boron-doped-diamond electrode (at 1.5V for 10min). 2,4-Diamino-1,3,5-triazine (2,4-DAT), methylbiguanide (MBG), 2-amino-4-methylamino-1,3,5-triazine (2,4-AMT) and 4-amino-2-imino-1-methyl-1,2-dihydro-1,3,5-triazine (4,2,1-AIMT) were identified by hydrophilic interaction chromatography (HILIC) with quadrupole time-of-flight mass spectrometry (QTOF-MS) and accurate mass fragmentation. However, the well-known transformation product guanyl urea (GU) could not be formed electrochemically. In samples from wastewater treatment plants (WWTP), 2,4-AMT and 2,4-DAT showed an increasing trend from influents to effluents, which implies formation of the TPs during WWT. MBG is also formed by hydrolysis of MF and therefore didn't show this trend in WWTPs. Compared to GU, the concentrations of other TPs are generally three orders of magnitude lower. MBG and 2,4-DAT were also detected in surface water which was impacted by waste water, while 4,2,1-AIMT could not be detected in any sample. The concentrations of MF were in an expected range for influent (14 to 95μg/l), effluent (0.7 to 6.5μg/l), surface water (up to 234ng/l) and tap water (34ng/l). GU concentrations, however, were in one of the two investigated WWTP much higher in the influent (between 158μg/l and 2100μg/l) than in the effluent (between 26 and 810μg/l). This is a rather unexpected result which has not been reported yet. Obviously, GU has been already formed in parts of the sewer system from MF or from other biguanide compounds like antidiabetics or disinfection chemicals. Furthermore, lower concentrations of GU in the effluents than in the influents indicate degradation processes of guanyl urea in the waste water treatment. [Display omitted] •Electrochemical generation of metformin (MF) TPs•Identification of MF TPs by LC-high-resolution MS•Detection of MF TPs in wastewater and surface water